Measurement of strange baryon-antibaryon interactions with femtoscopic correlations - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; et al. (Physics letters, 2020)
Two-particle correlation functions were measured for p (p) over bar, p (Lambda) over bar, (p) over bar Lambda, and Lambda(Lambda) over bar pairs in Pb-Pb collisions at root sNN = 2.76 TeV and root sNN = 5.02 TeV recorded by the ALICE detector. From a simultaneous fit to all obtained correlation functions, real and imaginary components of the scattering lengths, as well as the effective ranges, were extracted for combined p (Lambda) over bar and (p) over bar Lambda pairs and, for the first time, for Lambda(Lambda) over bar pairs. Effective averaged scattering parameters for heavier baryon-antibaryon pairs, not measured directly, are also provided. The results reveal similarly strong interaction between measured baryon-antibaryon pairs, suggesting that they all annihilate in the same manner at the same pair relative momentum k*. Moreover, the reported significant non-zero imaginary part and negative real part of the scattering length provide motivation for future baryon-antibaryon bound state searches. (C) 2020 The Author(s). Published by Elsevier B.V.